Ross's place in the history of analytic philosophy. Issue 4 (3rd July 2016) - Kaspar, David
ABSTRACT: With the recent revival of moral intuitionism, the work of W. D. Ross has grown in stature. But if we look at some recent well-regarded histories, anthologies and companions of analytic philosophy, Ross is noticeably absent. This discrepancy of assessments raises the question of Ross's place in the history of analytic philosophy. Hans-Johann Glock has recently claimed that Ross is not an analytic philosopher at all, but is instead a 'traditional philosopher'. In this article, I will identify several undeniable features of analytic philosophy that Ross's work bears: a focus on linguistic analysis, great respect for pre-theoretical thoughts, the conviction that philosophy is a collaborative, piecemeal enterprise and so on. Such an investigation, I claim, reveals two historically significant results: Ross was the first ethicist to fully draw from commonsense beliefs about morality in light of characteristic analytic considerations to secure his theory. Two, concerning the matter of whether the notions 'right' and 'good' are reducible to other notions, Ross appears to have been right: 'right' and 'good' are irreducible notions. The classical analytic metaethicists, who based their entire research programme on the promise of finding suitable reductive semantic analyses of 'right' and 'good', were wrong. These results, I believe, suffice to secure W. D. Ross a high place in the history of analytic philosophy.